2019
DOI: 10.1055/s-0037-1611575
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Intramolecular α-C–H Amination via Ring-Opening Cyclization Strategy to Quinazolin-4-ones: Development and Application in Rutaecarpine Synthesis

Abstract: A copper-catalyzed intramolecular α-C–H amination has been developed for the synthesis of quinazolin-4(3H)-one derivatives from commercially available isatoic anhydride and primary and secondary benzylamines via ring-opening cyclization (ROC). This method shows good functional group tolerance and allows access to a range of 2-aryl, 2-alkyl, and spiroquinazolinone derivatives. However, 2-methylquinazolin-4(3H)-one was synthesized from 2-amino-N-isopropylbenzamide by C–C bond cleavage, and N-benzyl-2-(methylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…In the past few decades, C–H activation leading to C–N bond formation has emerged as a powerful tool for the synthesis of nitrogen-containing bioactive molecules and pharmaceutically important compounds. , Very recently, radical chemistry has gained importance due to its sustainable features, and, in particular, “N” radical species have gained importance in their applicability in C–N bond formation, specifically with photo/electrotechniques. Among them, iminyl radicals represent valuable synthons among N-centered radicals .…”
mentioning
confidence: 99%
“…In the past few decades, C–H activation leading to C–N bond formation has emerged as a powerful tool for the synthesis of nitrogen-containing bioactive molecules and pharmaceutically important compounds. , Very recently, radical chemistry has gained importance due to its sustainable features, and, in particular, “N” radical species have gained importance in their applicability in C–N bond formation, specifically with photo/electrotechniques. Among them, iminyl radicals represent valuable synthons among N-centered radicals .…”
mentioning
confidence: 99%
“…5–9 In the past decade numerous efforts have been devoted to their construction, largely expanding the synthetic strategies towards quinazolinone-fused polycylic skeletons. These synthetic strategies include radical addition to inactivated alkenes installed on the parent quinazolinone and intramolecular annulation, 10 N -arylation of 2-aryl quinazolinones through C–H activation, 11 decarboxylative cyclization of isatins or their equivalents with heterocycles, 12 oxidative or reductive cyclization of o -nitrogen-containing benzaldehydes or their derivatives with heterocycles 13 and so on. 14–16 Despite being concise, green and efficient, these strategies could not meet the need for flexible access to diverse bioactive natural products possessing quinazolinone-[2,3]-fused polycyclic skeletons (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Isatoic anhydride is a cheap and commercially available compound that is a raw material for the synthesis of pharmaceuticals, agrochemicals and dyes, as well as an intermediate in the production of herbicide, Bentazone. The chemistry of isatoic anhydride and its reaction with amines has been investigated in detail [ 36 , 37 , 38 , 39 ]. We found that isatoic anhydride undergoes ring opening upon heating with various amines to produce 2-amino- N -alkylbenzamides, which can react with aldehydes [ 40 , 41 , 42 ] or orthoesters [ 43 , 44 , 45 , 46 ] and 2-formylbenzoic acid [ 47 , 48 , 49 ] to produce quinazolinones and isoindoloquinazolinones, respectively ( Scheme 1 a,b).…”
Section: Introductionmentioning
confidence: 99%